The Correlation Between Intra-Abdominal Pressure and Tolerance to Postoperative Hyperthermic Intraperitoneal Chemotherapy for Pseudomyxoma Peritonei - Yu, Junye; Yu, Lifei; Su, Lin; Shi, Ying (Frontiers in Surgery, 2022)
Objective: To evaluate the correlation between pain intensity and comfort level in patients with pseudomyxoma peritoneum (PMP) before and after hyperthermic intraperitoneal chemotherapy (HIPEC). Methods: From June 2018 to June 2019, patients who underwent HIPEC for PMP after surgical treatment in our institute were selected. The intra-abdominal pressure (IAP) and pain intensity (PI) before and after HIPEC were recorded, and the correlation between them was analyzed. Results: Seventy-four patients received HIPEC 253 times. IAP and PI were significantly higher after perfusion than before perfusion (P < 0.05). When IAP < 12 cmH2O, the change of PI was not correlated to the increase of IAP, and the patient tolerated the treatment. However, when IAP > 12 cmH2O, the increase of PI was significantly associated with IAP and cause significant discomfort during the treatment. Conclusion: IAP may be a monitoring index for the comfort of PMP patients during the postoperative HIPEC treatment.